EFFECT OF CHICORY LEAF EXTRACT SEED HARDENING CUM FOLIAR SPRAY TO IMPROVE RESULTANT SEED QULAITY IN SESAME (Sesamum indicum L.) cv. TMV 3 UNDER RAINFED CONDITION. - B. Sunil Kumar, G. Sathiya Narayanan,; R. Anandan, M. Prakash, (Horticultural Biotechnology Research)
An evaluation was carried out to study the effect pre sowing seed treatment and foliar spay with chicory leaf extract on resultant seed quality characters of sesame cv TMV 3. The bulk seeds were graded for uniformity using appropriate round perforated metal sieves of sizes of 5/64" size sieve and were imposed various concentration of chicory leaf extract presowing treatment coupled with foliar spray at different concentration under drought condition. After harvest the resultant seeds were evaluated for its seed qualities. The results revealed that the that the Chicory @ 20 % Pre sowing seed treatment + Chicory foliar spray @ 30 % during pod filling stage significantly increased the resultant seed quality characters of the sesame, when compared to other concentration and control.